To solve this problem, we need to note the definition of (fg)(x).
(fg)(x) is defined to be f(x)g(x), which is, essentially, the product of two fractions. On a similar note, (f o g)(x) would mean something different, in case you meant that.
With that said, all you have to do is replace and expand.
f(x)g(x) = [x^2 - 2x][5 - x] = 5x^2 - x^3 - 10x + 2x^2
= 7x^2 - x^3 - 10x
If, however, you meant (f o g)(x), then this is defined to be f(g(x)).
f(g(x)) = f(5 - x)
At this point, you replace ALL occurrances of x in f(x) with 5-x.
f(5 - x) = [5 - x]^2 - 2[5 - x] = [25 - 10x + x^2] - 10 + 2x
= 15 - 8x + x^2
2006-12-12 16:04:07
·
answer #1
·
answered by Puggy 7
·
0⤊
0⤋
I think what you're being asked for is the compound function f(g(x)). There are several different notations for this and it tends to get confusing.
Just 'plug in' 5-x for every occurrance of x in f(x) to get
(5-x)² - 2(5-x) = 25 - 10x + x² - 10 + 2x = x² - 8x + 15
Hope that helps
Doug
2006-12-12 16:03:10
·
answer #2
·
answered by doug_donaghue 7
·
0⤊
0⤋
I got -x^3 + 7x^2 - 10x = -x(x^2 - 7x + 10)
2006-12-12 16:04:22
·
answer #3
·
answered by S. B. 6
·
0⤊
0⤋
(fg)(x) = f(x)*g(x)
= (x^2 -2x)(5-x)
= 5x^2 - 10x - x^3 + 2x^2
= -x^3 + 7x^2 - 10x
2006-12-12 15:59:11
·
answer #4
·
answered by MsMath 7
·
3⤊
0⤋
is it f(g(x))
then (5-x)^2-2(5-x)
=25-10x+x^2-10+2x
=x^2-8x+15
if it is fog(x)
it is x^3-8x^2+15x
if it is f(x)*g(x)
-x^3+7x^2-10x
2006-12-12 16:01:54
·
answer #5
·
answered by raj 7
·
0⤊
0⤋
Is this composite functions?
(fg)(x)
(5-x)^2-2x
25-x^2-2x
2006-12-12 16:04:26
·
answer #6
·
answered by SHIBZ 2
·
0⤊
0⤋
Do you mean "find f(g(x))" ?
In that case, replace any "x" you find in f(x) with g(x) (replace then with 5-x) then solve.
2006-12-12 15:59:24
·
answer #7
·
answered by Jen B 2
·
0⤊
0⤋